Effects of ribose supplementation on repeated sprint performance in men - Berardi, J. M.; Ziegenfuss, T. N. (The Journal of Strength and Conditioning Research, 2003)
This study used a randomized, placebo-controlled, crossover design to evaluate the effects of oral ribose supplementation on short-term anaerobic performance. After familiarization, subjects performed 2 bouts of repeated cycle sprint exercise (six 10-second sprints with 60-second rest periods between sprints) in a single day. After the second exercise, bout subjects ingested 32 g of ribose or cellulose (4 × 8-g doses) during the next 36 hours. After supplementation, subjects returned to the laboratory to perform a single bout of cycle sprinting (as described above). After a 5-day washout period, subjects repeated the protocol, receiving the opposite supplement treatment. Ribose supplementation lead to statistically significant increases in mean power and peak power in sprint 2 (10.9 and 6.6%, respectively) and higher (although not significant) absolute values in sprints 1, 3, and 4. In conclusion, ribose supplementation did not show reproducible increases in performance across all 6 sprints. Therefore, within the framework of this investigation, it appears that ribose supplementation does not have a consistent or substantial effect on anaerobic cycle sprinting.